The effect of explicit and implicit online self-compassion interventions on sleep quality among Chinese adults: A longitudinal and diary study - Sheng, Haili; Wang, Ruibing; Liu, Conghui (Frontiers in Psychology, 2023)
Objective This study aimed to investigate the effects of explicit and implicit online intervention methods for self-compassion on improving sleep quality among Chinese adults. Methods A total of 328 adult participants were recruited to complete the Pittsburgh Sleep Quality Questionnaire and Self-compassion Scale, and 168 participants were randomly assigned to one of three different conditions: two self-compassion intervention groups (self-compassion writing intervention asked participants to write several sentences with self-compassion, and self-compassion combination intervention asked participants to combine words into complete sentences with self-compassion) and one control group. After 1 week of online self-compassion intervention with daily sleep quality measured simultaneously, 150 participants completed the posttest of the Pittsburgh Sleep Quality Questionnaire and Self-Compassion Scale. Results The pretest and posttests results showed that the self-compassion level and sleep quality of the self-compassion writing intervention group were significantly better than those of the control group. However, there was no significant difference between the self-compassion combination intervention group and the control group. For the diary tracking results, sleep quality was significantly better for both the self-compassion writing intervention group and self-compassion combination intervention group than the control group, however, the self-compassion writing intervention group showed great improvements. Conclusion Both self-compassion writing and combination interventions were effective in improving sleep quality, and the effect of self-compassion writing was more stable.